Where the wild things are --and other Maurice Sendak stories - Where the wild things are (Motion picture); Schindel, Morton; Deitch, Gene.; Riss, Sheldon; Schickele, Peter; King, Carole, 1942-; Sendak, Maurice; Sendak, Maurice; Sendak, Maurice; Sendak, Maurice; Weston Woods Studios; New Video Group ([Weston, Conn.] : Weston Woods : Distributed by New Video, 2001)
In 'Where the wild things are' Max is sent to bed without any dinner. He sails off to a world inhabited by weird creatures. 'The nutshell kids' are the songs Alligators all around, Pierre, One was Johnny & Chicken soup with rice, taken from the film Really Rosie-- dance through the alphabet, good manners, numbers and the months of the year. 'In the night kitchen': Mickey is awakened by noises in the night. Who's in the kitchen?
Collective title from disc and menu screen.
Based on books written and illustrated by Maurice Sendak.
Originally released as short films in 1973, 1976, 1987.
Extras: Getting to know Maurice Sendak (1985; ca. 6 min.) ; read along; Where the wild things are (Spanish language version); trailer.
[1st work] music & narration, Peter Schickele ; [2nd work] music by Carole King ; [3rd work] music, Angelo Michajlov ; narration, Peter Schickele.
MPAA rating: recommended for ages 3-8.
Keywords: Sendak, Maurice -- Film and video adaptations; Imagination in children -- Juvenile drama; Music -- Poetry -- Juvenile drama; Noise -- Juvenile drama; Imagination -- Drama; Music -- Drama; Poetry -- Drama; Animated films; Children's films